Hsa-miR-889-3p promotes the proliferation of osteosarcoma through inhibiting myeloid cell nuclear differentiation antigen expression - Dawei Ge (Biomedicine & Pharmacotherapy, 2019)
Osteosarcoma accounts for about 0.2% in human malignant solid tumors. The mortality and metastatic rates of osteosarcoma remain relatively high. MicroRNA (miRNA) is a kind of non-coding small-molecular RNA discovered in recent years. Various studies have identified the involvement of miRNA in the occurrence and development of tumor as an oncogene or tumor-suppressor gene. This study aims to investigate the effect of hsa-miR-889-3p on the progression of osteosarcoma and its underlying mechanism. Through the bioinformatics methods, we first found that hsa-miR-889-3p was upregulated in osteosarcoma, and it was a prognostic risk factor for osteosarcoma. Additionally, the gene set enrichment analysis (GSEA) revealed that hsa-miR-889-3p mainly affected cell cycle progression and proliferation of osteosarcoma. To verify the bioinformatics results, regulatory effects of hsa-miR-889-3p on osteosarcoma both in vitro and in vivo experiments were investigated. It is found that hsa-miR-889-3p could promote the proliferation of osteosarcoma cells though regulating cell cycle progression. Tumor size and growth rate of osteosarcoma were influenced by hsa-miR-889-3p in xenograft models. To further explore its potential mechanism, the target gene of hsa-miR-889-3p was predicted. Furthermore, hsa-miR-889-3p was confirmed to inhibit the expression of myeloid cell nuclear differentiation antigen (MNDA) in a targeted manner. In conclusion, hsa-miR-889-3p could promote the proliferation of osteosarcoma through inhibiting MNDA expression, which provides a potential therapeutic strategy in treatment for osteosarcoma.